Navigating through learning tensions at the front end: How firms can motivate paradoxical thinking when screening the creativity of ideas - Tobias Röth; Sven Heidenreich; Fiona Schweitzer; Patrick Spieth (R&D Management, 2024)
Idea screening is crucial as it must select the most promising ideas that are best suited to increase front-end success. Although paradox theory indicates that learning tensions characterize the evaluation and screening of idea creativity, we know little about how idea screeners navigate through the associated competing demands. In response, we investigate the effects of idea screeners' paradoxical thinking on the assessment of the creativity of ideas as well as its motivational antecedents of paradoxical thinking. By analyzing a survey ( N 0.167em=0.167em326) and an experiment ( N 0.167em=0.167em292), we show that paradoxical thinking increases front-end success and both dimensions of idea creativity (encompassing meaningfulness and novelty). In turn, by creating a motivational context (comprising decision autonomy, encouragement to take risks, and tolerance for mistakes), firms can provide the antecedents to adopt paradoxical thinking. Our study contributes to and extends the literature on screening idea creativity and paradox theory.
Keywords: 650